2014
DOI: 10.1155/2014/636839
|View full text |Cite
|
Sign up to set email alerts
|

Contribution ofα,β-Amyrenone to the Anti-Inflammatory and Antihypersensitivity Effects ofAleurites moluccana(L.) Willd.

Abstract: The aim of the study was to analyze the constituents of the dichloromethane fraction obtained from A. moluccana and also to evaluate the anti-inflammatory and antinociceptive properties of α,β-amyrenone isolated from A. moluccana in mice. The dichloromethane fraction was evaluated by gas chromatography and submitted to purification. The mixture of α,β-amyrenone was isolated and then evaluated using the carrageenan-induced paw-oedema or pleurisy and CFA-induced arthritis models in mice. Five triterpenes, α,β-am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 36 publications
1
11
0
1
Order By: Relevance
“…Both compounds have been reported to possess several pharmacological effects (e.g., anti-inflammatory, antinociceptive activities together with lipase, α-glucosidase, and α-amylase, inhibitory activities) [ 20 ]. In addition, α-amyrenone has also shown strong virucidal activity against HIV-1 reverse transcriptase in a low IC 50 value equal to 3.3 µM.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Both compounds have been reported to possess several pharmacological effects (e.g., anti-inflammatory, antinociceptive activities together with lipase, α-glucosidase, and α-amylase, inhibitory activities) [ 20 ]. In addition, α-amyrenone has also shown strong virucidal activity against HIV-1 reverse transcriptase in a low IC 50 value equal to 3.3 µM.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The chemical formula of α-amyrin(3α-hydroxy-urs-12-en-3-ol) is C 30 H 50 O (Figure 2), and its melting point is 184-186°C [103]; the chemical formula of β-amyrin(3β-hydroxy-olean-12-en-3-ol) is C 30 H 50 O (Figure 2) [106][107][108][109][110][111][112] and its melting point is 189-191°C [84]. Quintão et al (2014) demonstrated that AMY interferes in both acute and chronic inflammatory processes in mice by reducing mechanical hypersensitivity, mechanical sensitization, and oedema development in arthritis [86]. In a study by Krishnan et al (2014), significant decrease in edema was observed in rats by the administration of β-amyrin in a dose-dependent manner.…”
Section: Tomato Triterpenoidsmentioning
confidence: 99%
“…Many triterpenoids are known for exhibiting similar significant pharmacological properties; lupeol for example is known to have properties that significantly influence anti-inflammatory activities [86]. Lupeol (Lupa-21, 20(29) dien 3 beta-ol) is a naturally occurring pentacyclic triterpene (also known as Fagarsterol) under the lupane triterpene family, predominantly present in mango [87,88].…”
Section: Mango Lupane Triterpenesmentioning
confidence: 99%
“…A study involving the oral administration of α-β-amyrenone mixture to mice demonstrated its ability to reduce mechanical hypersensitivity and carrageenan-induced paw edema, and interference with neutrophils migration was studied as well. [ 9 ]. Our group has also reported that the same mixture inhibited the production of nitric oxide and Interleukin 6 (IL-6) and induced the production of IL-10 in murine macrophages J774 stimulated by Lipopolysaccharide (LPS), in addition to the inhibition of cyclo-oxygenase-2 (COX-2) expression.…”
Section: Introductionmentioning
confidence: 99%